Balkan Political Cooperation: Internal Impulses and External Factors - Bakalova, Maria; Parvanov, Anton (Research Papers, 2019)
The paper studies regional cooperation on the Balkans seeking positive instances back in history and focusing on the developments since the end of the Cold war. It seeks to answer the question “Why Balkan political cooperation has been thwarting in the last three decades?” Mostly answers are sought in historical past and experience from previous interactions and/or influence and intervention from extra-regional (f)actors. Our claim, however, is that answers should also be sought on regional and internal political level in the motivation and behavior of regional actors.